2007
DOI: 10.1103/physreve.75.026206
|View full text |Cite
|
Sign up to set email alerts
|

Variability-sustained pattern formation in subexcitable media

Abstract: Starting with a subexcitable net of FitzHugh-Nagumo elements it is shown that parameter variability (diversity) is able to induce pattern formation. These patterns are most coherent for an intermediate variability strength. This effect is similar to the well-known spatiotemporal stochastic resonance generated by additive noise in subexcitable media. Furthermore, variability is able to induce a transition to an excitable behavior of the net. This transition strongly depends on the coupling strength between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…One method of incorporating variability into Dictyostelium models is the use of agent-based models, with applications to processes such as cell sorting [ 45 ]. The role of coupling strength was investigated in [ 46 ] and [ 47 ]; effects such as target-spiral competition were shown in [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…One method of incorporating variability into Dictyostelium models is the use of agent-based models, with applications to processes such as cell sorting [ 45 ]. The role of coupling strength was investigated in [ 46 ] and [ 47 ]; effects such as target-spiral competition were shown in [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gosak [65] investigated the role of cellular variability on the occurrence of Ca wave propagation in a net of diffusively coupled cells, and confirmed a resonance-like response due to the cellular variability by analyzing the spatial profile via the autocorrelation function. Glatt et al [66] studied the pattern formation in subexcitable net of FitzHugh-Nagumo elements with parameter variability (diversity) being considered, an intermediate variability strength induced similar spatiotemporal stochastic resonance generated by additive noise in subexcitable media and transition induced by variability in coupling intensity is also observed. Surely, a local periodic forcing is also effective to generate a target-like wave in the network as well.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there are several reports about the effect of diversity on spatially extended systems. It was found that parameter variability is able to induce pattern formation [31] and resonance-like behavior [32] in an excitable square lattice. For spatially extended chaotic systems, it was also found that parameter variability has the ability to induce coherence resonance [33].…”
Section: Discussionmentioning
confidence: 98%